Xanthophyll cycling in the model diatom Phaeodactylum tricornutum - Paton, Andrew J., author; Peers, Graham, advisor; Reddy, Anireddy S. N., committee member; Nishimura, Marc T., committee member; Snow, Christopher D., committee member (Colorado State University. Libraries, 2026)
Diatoms are microalgae that are abundant across the globe, produce around 20% of atmospheric oxygen, and are increasingly relevant to industry for lipid and nutraceutical production. Through a separate evolutionary history from plants, diatoms possess several distinct photosynthetic pigments. As photosynthetic organisms, diatoms must balance harvesting enough light for photochemistry and dissipating harmful excess light through non-photochemical quenching (NPQ) of absorbed light energy. Diatoms primarily accomplish this by a toggle switch between carotenoid pigments called the xanthophyll cycle. Diatom NPQ is correlated with the photoprotective pigment diatoxanthin (Dtx) in high light, while greater photochemistry at lower light is correlated with diadinoxanthin (Ddx). The genes catalyzing this cycle had not been fully characterized. This dissertation sought to identify these genes and characterize pigment content, photophysiology, and cell fitness in their absence. First, Chapter 2 presents a promoter characterization method which showed three effective native promoters to use in Phaeodactylum tricornutum episomal expression and genetic manipulation. In Chapters 3 and 4, I show evidence that Phaeodactylum genes with homology to the zeaxanthin epoxidase (ZEP3) and violaxanthin de-epoxidase (VDE) genes of plants complete the diatom xanthophyll cycle, respectively. A zep3 mutant is unable to turn off the xanthophyll cycle once induced, accumulates Dtx, and has a constitutive NPQ phenotype. A vde mutant is unable to make Dtx, does not turn on NPQ and so is susceptible to damage from excess light. Consequently, both mutants have reduced growth in a variable light regime mimicking natural conditions. In Chapter 5, I directly compare these mutants' Photosystem II photochemical flux and carbon accumulation, which are linked through photosynthesis. The inability to perform reversible NPQ leads to some divergence in photophysiology and carbon accumulation. Notably, both vde and zep3 mutants accumulated more carbon per cell under sinusoidal light and nutrient stress compared to wild type. This is despite all strains having equal capacity to perform photochemistry. It appears that xanthophyll-based NPQ capacity regulates the absorption cross-section of PSII photochemistry through the photosynthetic antennae for harvesting light, especially during nutrient stress. These chapters further our understanding of how diatoms achieve ecological success. Diatom evolution of NPQ through the acquisition of genes related to those responsible for the xanthophyll cycle in the green lineage afforded them great flexibility in maintaining a balance of light harvesting and light dissipation in fluctuating light conditions, such as coastal habitats and estuaries where diatoms are still predominant today. The knowledge of the genetic basis of the diatom xanthophyll cycle furthered by this dissertation also provides an engineering target for improving diatom productivity in dense industrial culture, where competition between light harvesting and dissipation leads to productivity losses. Manipulation of NPQ capacity via controlled PtVDE and PtZEP3 expression could reduce these losses to allow for more efficient culture growth to make food, biofuels, and bioproducts.
Keywords: diatom; photosynthesis; xanthophyll cycle; non-photochemical quenching; algae; pigments